Extra-skeletal (periosteal Ewing's sarcoma) Ewing's sarcoma of distal femur of right leg in a 10 year old boy - A case report (Health Renaissance, 2011)
Extra-skeletal Ewing's sarcoma is quite uncommon.The most common locations of Ewing's sarcoma of bone include metaphysis and diaphysis of long bones and flat bones of shoulder and pelvic girdles. Here, we present a case of a 10 year-old school-going boy who had presented to the Orthopaedic Depatment of B.P.Koirala Institute of Health Sciences, Dharan, Nepal with the complaint of pain and swelling of pasterior aspect of disfal fourth of right thigh. Considering its rarity, we thought that this case needs to be reported. Keywords: Skeletal; Periosteum; Tumor; Sarcoma; Wide excision DOI: 10.3126/hren.v9i1.4364Health Renaissance, 2011: Vol.9 No.1:50-53